Evaluation of Thermal Conditions in Jeziory (The Wielkopolski National Park) - Szyga-Pluta, Katarzyna; Półrolniczak, Marek (Quaestiones Geographicae, 2013)
The purpose of this paper is to present selected methods of evaluation of thermal conditions in the Wielkopolski National Park and their initial characterization. The analysis was based on data from the automatic meteorological station in Jeziory measured during the period 2001-2010. The calendar of thermal classes graphically shows the variation in thermal conditions for each month and deviation from the standard adopted for the period concerned (Table 2). A good complement to the calendar seems the graphs of mean daily air temperature for months above and below the standards that enable their connection with the peculiarities of weather occurring in the area of Central Europe (Fig. 1). In addition to complete characterization of thermal conditions, specific number of days according to the average daily temperature ranges (Tavr): tavr. < 10°C, tavr. 10.1-15.0°C, tavr. 15.1-20.0°C, tavr. 20.1-25.0°C, tavr. 25.1-30.0°C and interdiurnal changes of average daily temperature (ΔTavr): Δtavr. < 2°C, Δtavr. 2.1-4.0°C, Δtavr. 4.1-6.0°C, Δtavr. >6.0°C were calculated (Table 3, 4). They were the basis for separating the year into thermal seasons (Table 5, Fig. 2). Ward’s method was used giving the best results in the case while both Tavr and ΔTavr were taken into consideration. The results obtained allow concluding that different methods of evaluation of thermal conditions applied separately do not give a full picture of thermal conditions of the area. Only a combination of results obtained using the Ward’s and calendar methods can give a complete thermal conditions characterization.